2012
DOI: 10.4103/0257-7941.103184
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic and in vitro antioxidant evaluation of fractions of methanol extract of Leea asiatica leaves

Abstract: Leea asiatica, a folk medicinal plant of India, is used in the treatment of worm infection and other oxidative stress-related disorders, traditionally. In the present study, the in vitro anthelmintic and in vitro antioxidant activity of different fractions of the methanol extract from the Leea asiatica leaves were evaluated. The fraction displayed significant anthelmintic activity against Indian adult earthworms (Pheretima posthuma). The ethyl acetate fraction showed a better paralysis activity (13.99 ± 0.59),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Leea asiatica has also been used as a folk medicine, especially in India, to treat worm infection, bone fracture, liver disorder, and oxidative stress-related diseases. Up to date, three published reports have described the biological effects of L. asiatica extracts, including anthelmintic and antioxidant-related nephroprotective and hepatoprotective activities [14,15,16], and no phytochemical study on this species has been attempted yet even though L. asiatica has been used as a traditional medicine, as have other Leea species. The identification of the phytochemicals of herbal medicine is very important because it can be used as a primary data for the prediction of biological effects, safety information, and clarification of medicinal use.…”
Section: Introductionmentioning
confidence: 99%
“…Leea asiatica has also been used as a folk medicine, especially in India, to treat worm infection, bone fracture, liver disorder, and oxidative stress-related diseases. Up to date, three published reports have described the biological effects of L. asiatica extracts, including anthelmintic and antioxidant-related nephroprotective and hepatoprotective activities [14,15,16], and no phytochemical study on this species has been attempted yet even though L. asiatica has been used as a traditional medicine, as have other Leea species. The identification of the phytochemicals of herbal medicine is very important because it can be used as a primary data for the prediction of biological effects, safety information, and clarification of medicinal use.…”
Section: Introductionmentioning
confidence: 99%
“…We have conducted a ethnomedicinal survey in Tripura, India and found that the plant is used to treat liver disorder by the ethnic people (Bhandary et al, 1995;Prasad et al, 2008;. In our previous investigation we reported that leaves of L. asiatica possess in vitro antioxidant, anthelmintic and nephroprotective activity (Sen et al, , 2012 (Manokaran et al, 2008;Singh et al, 1995). After 48 h of acetaminophen administration, the blood was collected under light ether anaesthesia and serum was separated by centrifugation of blood at 4000 × g, which was used for the biochemical estimations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the earthworms have been widely used for the initial study of in vitro anthelmintic activity [10]. According to Sen et al, substances that have anthelmintic activity on the earthworms is also effective against parasitic worms of human [11]. The present study exhibited the anthelmintic activity of SF4 is most potent to P. posthuma among the others even than the standard pyrantel.…”
Section: Discussionmentioning
confidence: 57%